2009
DOI: 10.1093/aje/kwn375
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Dietary Glycemic Index, Glycemic Load, and Fiber and Whole-Grain Intakes During Puberty to the Concurrent Development of Percent Body Fat and Body Mass Index

Abstract: The authors prospectively examined whether change in dietary glycemic index (GI), glycemic load (GL), fiber intake, or whole-grain intake during puberty is associated with concurrent change in percentage of body fat (%BF) or body mass index (BMI; weight (kg)/height)(2). Linear mixed-effects regression analyses were performed in 215 participants from the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) Study (Dortmund, Germany) who possessed weighed 3-day dietary records and anthropometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 42 publications
4
63
2
3
Order By: Relevance
“…Nonetheless, given that median values of dietary GI and GL appear to be among the highest in the Danish (range of median: 58.8-60.2 and 154-217, respectively) 15 and the present Japanese (range of median: 62.6-63.8 and 135.4-169.0, respectively) studies, where the expected association was in fact observed, dietary GI and GL may have been too low or distributed too narrowly in other studies in which the association was not observed (range of median: 51.7-59.8 and 62.8-145.0, respectively). [10][11][12][13][14] We do not know why we found the expected association for dietary GL only and not GI; however, both the quality and quantity of dietary carbohydrate rather than quality alone may be important for the development of overweight. The limited number of observational studies in Western countries do not generally support the favorable effect of dietary fiber in measures of obesity, [12][13][14][36][37][38] with several exceptions.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…Nonetheless, given that median values of dietary GI and GL appear to be among the highest in the Danish (range of median: 58.8-60.2 and 154-217, respectively) 15 and the present Japanese (range of median: 62.6-63.8 and 135.4-169.0, respectively) studies, where the expected association was in fact observed, dietary GI and GL may have been too low or distributed too narrowly in other studies in which the association was not observed (range of median: 51.7-59.8 and 62.8-145.0, respectively). [10][11][12][13][14] We do not know why we found the expected association for dietary GL only and not GI; however, both the quality and quantity of dietary carbohydrate rather than quality alone may be important for the development of overweight. The limited number of observational studies in Western countries do not generally support the favorable effect of dietary fiber in measures of obesity, [12][13][14][36][37][38] with several exceptions.…”
Section: Discussionmentioning
confidence: 57%
“…[10][11][12][13][14] We do not know why we found the expected association for dietary GL only and not GI; however, both the quality and quantity of dietary carbohydrate rather than quality alone may be important for the development of overweight. The limited number of observational studies in Western countries do not generally support the favorable effect of dietary fiber in measures of obesity, [12][13][14][36][37][38] with several exceptions. 39 This is consistent with the null findings in the present Japanese study.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations